Round window membrane permeability to golimumab in guinea pigs: A pilot study. (25th June 2013) - Ghossaini, Soha N.; Liu, Jenny P.; Phillips, Brett
Abstract : Objectives/Hypothesis: Autoimmune inner ear disorder is one of a few types of sensorineural hearing loss that is treatable and potentially reversible. Treatment involves oral steroids and methotrexate. Other treatment modalities have been tried with variable success. All such treatments are systemic, with inherent side effects limiting their effectiveness. Recently, tumor necrosis factor (TNF)‐α blockers have been suggested as a modality of treatment. The objective of this study was to assess the round window membrane permeability to golimumab, a TNF‐α blocker. This study is the first to look at the feasibility of local golimumab delivery into the inner ear, which may allow for targeted immune modulation of autoimmune inner ear disorders without the consequences of systemic treatment. Study Design: This is a single‐blinded, placebo‐controlled, pilot study using guinea pigs to assess round window membrane permeability to golimumab. Methods: Golimumab was instilled into the guinea pigs' middle ear. Inner ear fluid was sampled through the round window membrane after approximately 30 minutes of drug exposure. Golimumab presence in the inner ear was assessed by enzyme‐linked immunosorbent assay in both drug‐treated and control ears. Results: Higher concentrations of golimumab were detected in the inner ear fluid samples of golimumab‐exposed ears than in the control ears. The difference was statistically significant ( P < .001). Conclusions: Golimumab crosses the round window membrane and is detected in measurable concentrations in the inner ear fluid after 30 minutes of exposure to the membrane. Further studies are needed to learn its pharmacokinetics and the time needed to reach optimal concentration in the inner ear. Level of Evidence: NA. Laryngoscope, 123:2840–2844, 2013